2008
DOI: 10.1213/ane.0b013e318181f013
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Age on the Dynamic Relationship Between End-Tidal Sevoflurane Concentrations and Bispectral Index

Abstract: BACKGROUND:Age is an important determinant of the pharmacokinetic profile of inhaled anesthetics. The influence of age on the dynamic profile of sevoflurane's effect has not been well described. We performed this study to characterize the influence of age and other covariates on the dynamic relationship between sevoflurane end-tidal concentration (C ET ) and its effect measured by bispectral index (BIS). METHODS: Fifty patients, aged 3-71 yr, scheduled for minor surgery were prospectively studied. The BIS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 17 publications
5
21
0
1
Order By: Relevance
“…The k e0 was faster with the BIS than with the CSI, although the two values were not statistically different. Our results were similar to those reported in children whose K e0 value in the BIS was also greater than in the CSI, although the actual K e0 values of children are larger than those of adults [2,14] . Our mean individual K e0 value for the BIS was 0.36 min -1 , which is comparable to previously reported range (0.22-0.48 min -1 ) [15][16][17][18] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The k e0 was faster with the BIS than with the CSI, although the two values were not statistically different. Our results were similar to those reported in children whose K e0 value in the BIS was also greater than in the CSI, although the actual K e0 values of children are larger than those of adults [2,14] . Our mean individual K e0 value for the BIS was 0.36 min -1 , which is comparable to previously reported range (0.22-0.48 min -1 ) [15][16][17][18] .…”
Section: Discussionsupporting
confidence: 90%
“…The C eff50 and k e0 were expected to decrease with increasing age because age reduces the requirements of sevoflurane and increases the blood-brain equilibration times [14] . However, in our population, the covariate of age did not improve the goodness of fit.…”
Section: Discussionmentioning
confidence: 99%
“…We also separated the patients into two groups: 3e7 years (n ¼ 126) and 8e12 years (n ¼ 34) similar to Cortínez et al 18 The BIS value was 42.4 AE 12.6 for 3e7 years group and 45.1 AE 14.2 for 8e12 years group ( p ¼ 0.23). There was no significant difference between E'sevo and BIS in different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…18e20 Previous studies comparing the relationship between E'sevo and BIS in children appeared to be age dependent. 18,19 However, another study found no difference in BIS in children before induction, during maintenance, and on emergence compared with adult values, and suggested that BISguided anesthesia could improve the titration of anesthetics in children. 20 In this study, we examined the relationship between E'sevo and BIS in children.…”
Section: Discussionmentioning
confidence: 99%
“…Diese entspricht nach einer kurzen Latenz der Blutkonzentration [10]. Bei beiden Techniken muss initial mit einer höheren Dosis "angeflutet" werden.…”
Section: Dosierung Und Aufrechterhaltungunclassified